2006
DOI: 10.1002/14651858.cd004334.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for promoting booster seat use in four to eight year olds travelling in motor vehicles

Abstract: Available evidence suggests that interventions to increase use of booster seats among children age four to eight years are effective. Combining incentives (booster seat discount coupons or gift certificates) or distribution of free booster seats with education demonstrated marked beneficial outcomes for acquisition and use of booster seats for four to eight year olds. There is some evidence of beneficial effect of legislation on acquisition and use of booster seats but this was mainly from uncontrolled before-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 31 publications
1
30
1
1
Order By: Relevance
“…Parents were 1.7 times more likely to correctly use child safety seats at the 1 year post-test and were almost two times more likely to be able to indicate correct height and weight to safely transition their child to a seat belt following the intervention regardless of income, education or parent age. These findings build on previous intervention studies which suggest that education is a key dimension for increasing parent knowledge and use of safety seats (Ehiri et al, 2006;Johnston et al, 2000).…”
Section: Variablesupporting
confidence: 81%
See 3 more Smart Citations
“…Parents were 1.7 times more likely to correctly use child safety seats at the 1 year post-test and were almost two times more likely to be able to indicate correct height and weight to safely transition their child to a seat belt following the intervention regardless of income, education or parent age. These findings build on previous intervention studies which suggest that education is a key dimension for increasing parent knowledge and use of safety seats (Ehiri et al, 2006;Johnston et al, 2000).…”
Section: Variablesupporting
confidence: 81%
“…Approximately 86% of children who should be restrained in a booster seat are restrained in seat belts (Simpson et al, 2003). In fact, parents may not know that seat belts offer poor protection for a school-aged child (Ehiri et al, 2006;Rivara et al, 2001;Safe Kids Canada, 2004;Transport Canada, 1998;. A large Canadian study found that 84% of parents believe their children are too big or too old for booster seats (Safe Kids Canada, 2004).…”
Section: Issues Of Safety Seat Misusementioning
confidence: 99%
See 2 more Smart Citations
“…The authors thank Dr Ebel for her in-depth analysis of our review on interventions to increase use of booster seats among 4-8 year olds who travel in motor vehicles (1). Her observation on the need for studies that measure sustained increases in booster seat use is very important.…”
Section: Potential Conflict Of Interestmentioning
confidence: 99%